Association between red blood cell distribution width and mortality in patients with metastatic brain tumors: A retrospective single-center cohort study - Sim, Ji-Hoon; Park, Yong-Seok; Ha, Seungil; Kim, Sung-Hoon; Kim, Joung Uk (Frontiers in Oncology, 2022)
Metastatic brain tumor has been associated with high mortality and poor prognosis. However, information on indicators predicting surgical prognosis in patients with brain metastases is limited. This study aimed to investigate the association between preoperative red blood cell distribution width (RDW) and mortality in patients who underwent surgery for metastatic brain tumors. This study analyzed 282 patients who underwent metastatic brain tumor surgery between August 1999 and March 2020. Patients were divided into two groups based on preoperative RDW cut-off values (<13.2 and ≥13.2). The surgical outcomes were compared between the two groups. Additionally, we performed Cox regression analysis to assess the association between preoperative RDW and 1-year and overall mortality. There were significant differences in 180-day mortality (6.2% vs. 28.7%, P<0.001), 1-year mortality (23.8% vs. 46.7%, P<0.001), and overall mortality (75.0% vs. 87.7%, P=0.012) between the two groups. In the Cox regression analysis, RDW ≥ 13.2 was significantly associated with higher 1-year mortality (adjusted hazard ratio [HR], 2.14; 95% confidence interval [CI], 1.38–3.30; P<0.001) and overall mortality (HR, 1.44; 95% CI, 1.09–1.90; P=0.010). Preoperative RDW is strongly associated with high mortality in metastatic brain tumor surgery.